Laboratory Tests of the Control of the Child Seats using Method for the Vibration Comfort of Children Transported in Them - Damian Frej; Andrzej Zuska; Emilia Szumska (Communications - Scientific letters of the University of Zilina, 2021)
The article presents results of the laboratory studies of the impact of the child seats mounting method on the vibration comfort of children transported in them. The tested child seats were mounted forward facing the rear seat of a passenger car. The A seat was fastened with the ISOFIX base, while the B seat was fastened with standard car seat belts. During the tests, values of the vertical vibrations were measured on the seat of the child seat, the rear seat of the vehicle and the ISOFIX base. It was noted that the analyzed system, may be characterized by two different vibration transmission chains, which depend on the child seat mounting system (classic seat mounting system and ISOFIX system). These studies show the negative impact of using the ISOFIX base, which is confirmed by the Root Mean Square (RMS) values and the Vibration Dose Value (VDV), determined for the "A" seat secured with the ISOFIX base that were higher than the RMS and VDV for the "B" classic mounted seat.